Effect of the suspension of the J&J COVID-19 vaccine on vaccine hesitancy in the United States. Issue 3 (24th January 2022) - Hsieh, Yuli Lily; Rak, Summer; SteelFisher, Gillian K; Bauhoff, Sebastian
Abstract: On April 13, 2021, U.S. authorities announced an investigation into potential adverse events associated with the Johnson & Johnson (Janssen, J&J) COVID-19 vaccine and recommended "a pause in the use of this vaccine out of an abundance of caution." We examined whether public attitudes toward COVID-19 vaccination shifted after this recommended suspension using an interrupted time series with data from the Census Bureau's Household Pulse Survey, which was fielded bi-weekly between January 6 and April 26, 2021. We found no significant changes in trends of the proportion of the U.S. adult population hesitant about getting a COVID-19 vaccine, but a significant increase in concerns about safety and efficacy of COVID-19 vaccines among the already hesitant population.